Effects of light qualities on the growth and photosynthetic characteristics of Sorbus tianschanica Rupr. seedlings - Xiong Lv; Shanchao Zhao; Hong Chen; Xin Zhao (PLoS ONE, 2026)
Light quality is an important environmental factor influencing plant growth and development, but its effects on functional traits and physiological processes in woody seedlings remain unclear. In this study, Sorbus tianschanica Rupr. seedlings were grown under four colored film treatments (red, blue, green, and white) to assess their effects on growth, leaf anatomy, chloroplast ultrastructure, photosynthetic performance, enzyme activities, and carbohydrate accumulation. Blue film significantly increased seedling height growth rate, whereas red film promoted ground diameter growth ( P < 0.05). Stomatal aperture, size, and density were highest under blue film. Leaves under blue and red films were thicker and more compact, while those under green film were thinner and less structured. Chloroplasts in the blue treatment showed well-organized grana and stroma lamellae, whereas those under green film were disorganized. Photosynthetic pigment contents were higher under red, blue, and green films than under white film ( P < 0.05). Net photosynthetic rate ( Pn ), stomatal conductance ( Gs ), and transpiration rate ( Tr ) were higher under blue and red films, and lowest under green film. Light response parameters, including maximum net photosynthetic rate ( Pn max ) and light saturation point ( LSP ), were also higher under blue and red treatments. Chlorophyll fluorescence parameters ( ΦPSII and qP ) and photosynthetic enzyme activities were highest under blue film. Blue film also increased carbohydrate accumulation, particularly in leaves and roots. Multilevel fuzzy comprehensive evaluation (MFCE) indicated that blue film had the highest overall performance. These results suggest that light quality affects seedling growth through changes in leaf structure, chloroplast organization, photosynthetic capacity, and carbon assimilation, with blue light providing the most favorable conditions for Sorbus tianschanica Rupr. seedlings.